CHARACTERIZATION OF SORGUM MUFFIN (Sorghum bicolor) OF KD 4 VARIETY WITH SOAKING GRAIN AND SORGUM FLOUR CONCENTRATION TREATMENT - Ita Yustina; Ana Nurhasanah; SS. Antarlina (Jurnal Penelitian Pascapanen Pertanian, 2021)
By processing sorghum grains into flour, the use of sorghum grains to support food diversification can be made more varied. The research objective was to determine the physical and chemical properties of sorghum muffins and changes of physical properties of sorghum muffins during storage. The research uses a completely randomized design with two factor, grain soaking duration (hours) and ratio of concentration of whole sorghum flours with gluten flour (%) and consists of nine treatments combination. The result shows that treatment has a significant effect on the power expansion, degree of brightness, fat, and preference for organoleptic properties. The best treatment was 24-hours of soaking, 25% whole sorghum flour, 75% gluten flour that produces expanded power at 138,83%, degree of brightness (L) at 67.03, redness (a) at +4.33, yellowness (b) at +27.37, water content of 12.59%, protein content of 6.95%, fat content of 2.46%, score of color at 3.20, texture score at 3.13, aroma score at 3.16, taste score at 3.24, and for overall acceptance at 3.53 (like). Changes of physical properties of sorghum muffins during storage for 3 days can be explained with the linear equation. For all parameter (weight loss, volume loss, brightness loss), the value of constant a in the equation of sorghum muffin was lower than control muffin that indicated quality loss of sorghum muffins is higher than control muffin. Increasing the concentration of sorghum flour resulted a decrease in the quality of the muffins. The soaking treatment of the seeds in making sorghum flour can maintain the quality of the muffin.